Derivatives of Multivariate Bernstein Operators and Smoothness with Jacobi Weights. (20th February 2012) - Wang, Jianjun; Peng, Zuoxiang; Duan, Shukai; Jing, Jia
Abstract : Using the modulus of smoothness, directional derivatives of multivariate Bernstein operators with weights are characterized. The obtained results partly generalize the corresponding ones for multivariate Bernstein operators without weights.